Pollen food syndrome amongst children with seasonal allergic rhinitis attending allergy clinic. Issue 2 (9th December 2015) - Ludman, Sian; Jafari‐Mamaghani, Mehrdad; Ebling, Rosemary; Fox, Adam T.; Lack, Gideon; Du Toit, George
Abstract: Background: There is limited information regarding the onset and sensitization patterns of pollen food syndrome (PFS) in children. The aim was to explore this within children referred to a specialist allergy clinic at a London Tertiary Hospital. Methods: A total of 54 patients with seasonal allergic rhinitis (SAR) were enrolled in equal numbers in three age groups; 0–5, 6–10, 11–15 years. Families completed a questionnaire on rhinitis, food symptoms and quality of life. Children underwent skin prick testing (SPT) to fresh fruits, nuts and a blood test for microarray analysis. Results: Clinical diagnosis of PFS was made in 26/54 (48%), increasing with age (group 1 = 3 (17%), group 2 = 9 (50%), group 3 = 14 (78%) (p = 0.03)). Microarray demonstrates children aged 2.8 years sensitized to pan‐allergens and 4.5 years symptomatic to pan‐allergens. Peach, cherry, carrot and strawberry SPT had the highest sensitivity and NPV at 100%. The sensitivity of PR10 molecules on microarray was 92%, PPV 62% and NPV 87%. Microarray confirmed 69% of allergens on clinical history compared to 61% by SPT. Microarray and SPT had a 19% false‐negative rate. The quality‐of‐life data showed moderate impact across all domains, and patients with PFS were significantly more likely to have increased anxiety over time spent preparing food (p = 0.029). Conclusions: We demonstrate that SAR occurs in children from 1.4 years and PFS from 4.5 years with a changing pattern of pan‐allergen sensitization. Microarray and SPT have moderate concordance in confirming allergens. PFS impacts negatively on quality of life and should be assessed in all paediatric allergy patients.